IDENTIFICATION AND QUANTIFICATION OF LUPEOL IN DIPTERACANTHUS PATULUS (JACQ.) NEES BY HIGH PERFORMANCE LIQUID CHROMATOGRAPHY- PHOTO DIODE ARRAY METHOD - MRS.N.KANNIKAPARAMESWARI; DR.P.CHINNASWAMY (International Journal of Pharma and Bio Sciences, 2013)
Plants have many phytochemicals with various bioactivities, including antioxidant, anti-inflammatory and anticancer activities. Hence the study focuses on the identification and quantification Lupeol from the methanolic leaves extract of Dipteracanthus paulus (Jacq.) Nees. High Performance Liquid Chromatography with Photodiode array detector (HPLC-PDA) was used to analyse the compound of interest. The quantity of lupeol was calculated from the respective peak areas according to individual standard curves. The content of the compound in the extract was 0.04mg/g dry weight (0.004%). The results of present study confirm the presence of good percentage of Lupeol which supports the biological potency of the plant.